Offence-Presumptive Terms: A Troubling Category in Linguistic Offensiveness - Heffer, Chris (Language and Law / Linguagem e Direito, 2025)
This paper argues that there is a set of words, word senses and phrases that are not inherently offensive but that can lead the hearer to presume that they are offensive. The archetypal, though now somewhat problematic, case is the adjective niggardly (‘stingy’, ‘parsimonious’), but I also discuss two cases based on forensic casework: the metaphorical sense of the verb kneecap (bring to its knees); and the now aging catchphrase never mind the quality, feel the width (go for quantity over quality, used ironically). These offence-presumptive terms are a subcategory of Low-Occurrence Ordinary Terms (LOOTs). LOOTs are ordinary enough for the speaker to presume they will be understood and for the hearer to presume that they know or can infer the meaning, while at the same time infrequent enough not to be familiar to many hearers. Crucially, offense-presumptive LOOTs have lexical ‘neighbours’ in our mental lexicons that are either attested as, or are perceived to be, offensive. I argue that the presumption of offensiveness comes about because hearers apply autonomous intuitive reasoning to the unknown word, word sense or phrase. While in many cases of lexical inferencing, such intuitive reasoning can lead us to make a successful guess about the meaning of a word, in the case of offence-presumptive terms, the hearer is led astray. Moreover, in raising a claim of linguistic offence, claimants prime HR personnel to activate in their own minds an offensive frame for the term. I consider the implications of this novel category for forensic lexical analysis, the judgment of linguistic offence and the ethics of interpersonal communication.